Compression of Navigation Video Sequences Using Global Motion Estimation - Springer, Dominic (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)
The estimation of global motion in video sequences is difficult, especially when motion between frames is of higher order and strong in magnitude. This thesis sets out to reliably and precisely estimate the motion of the map area in navigation video sequences. Five essential challenges are considered and solved: - Estimation of precise map motion parameters - Estimation of map motion parameters under difficult conditions - Integration strategy into a video codec like HEVC/H.265 - Integration of the overall solution into a larger framework - Fulfillment of given real-time processing requirements As demonstrated, the designed global motion estimation scheme yields significant bitrate savings when integrated into an HEVC/H.265 video encoder. The developed software modules are widely open for configuration, scale adaptively to the available CPU resources, and have been successfully used for a variety of automotive testing scenarios.
Keywords: Datenkompression; Navigation; Bewegungsmessung